ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI DAN PENDAPATAN INDUSTRI BAKERY DI KOTA DENPASAR - Kamajaya, Arya Damar; Ayuningsasi, Anak Agung Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.12.TAHUN.2023, 2023)
This study aims to analyze the effect of capital and labor on the production and income of the bakery industry in Denpasar City. The data used in this study is primary data from conducting structured interviews with respondents. The research population is bakery entrepreneurs in Denpasar City. The sampling method used is purposive sampling. Based on the Slovin formula, a sample of 210 respondents was determined. The analysis technique used is path analysis. The results showed that capital and labor have a positive effect on production in the bakery industry in Denpasar City. It means that the higher the capital and labor, the higher the products produced. Capital, labor, and production have a positive effect on the income of the bakery industry in Denpasar City. It means that the higher the capital, labor, and production, the higher the income generated. Production mediates the effect of capital and works on the income of the bakery industry in Denpasar City. That is, when capital and labor increase, it can increase income if production increases.